Public Service Motivation and Ethical Behavior amid Challenge Stressors - Ghimire, Ramesh Raj (The Lumbini Journal of Business and Economics, 2023)
This study aims to investigate the relationship between Public Service Motivation (PSM) and ethical or unethical behaviors in the context of work stressors. A survey was conducted on 300 public sector employees in Nepal using structured questionnaires with a seven-Likert scale. The study used a deductive approach to examine the association between PSM and ethical behavior in situations of challenge stressors at work. The research found that high levels of PSM are linked to high levels of ethical behavior intentions, and this relationship is further strengthened in the presence of challenge stressors as a positive moderator. The study also highlights the challenges of self-reported measures and social desirability bias when observing ethical or unethical behavior. The primary variables observed in the public sector of Nepal were PSM, ethical behavior, and challenge stressors, with only three variables and a limited sample size being the major limitations. Overall, this study suggests that the use of PSM as a tool and creating workplace challenges may contribute to improving ethical conduct among public sector employees.